SENSING ANALYSIS OF PT PELABUHAN INDONESIA III (PERSERO) FOR DEVELOPING BUSINESS STRATEGIES TO MAINTAIN COMPETITIVE ADVANTAGE (The Indonesian Journal of Business Administration, 2019)
Pelindo 3 is a State-Owned Business Entity engaged in port services that offer Ship Services, Passenger Services, Goods Services, Loading and Unloading Services including Container, General Cargo, Dry Bulk and Liquid Bulk in International and Domestic, and Services related to Port ServicesWith the enactment of the mandate of Law No. 17/2008 on Shipping, Pelindo 3 which was previously a Port Authority turned into a Port Operator, the law also abolished the state sector's monopoly rights over ports and opened up broad opportunities for the private sector to take part in the supply business and / or port services.In its development, in addition to ratifying the Law on Shipping, the Government as the majority shareholder will also restructure by establishing a maritime holding sector and an APBMI effort will require the government to revise the Minister of Transportation Regulation on the Implementation and Exploitation of Loading and Loading Goods from and to Ships.In addition, up to now Pelindo 3 has not been able to achieve the company goals set in the Company's Long Term Plan (RJPP), according to Pelindo 3 management report data in 2018, Pelindo 3's market share in handling General cargo services, dry bulk cargo, bulk liquid cargo not reaching the target. only the container and container loading service market share reached the target but was still inferior to competitors.In connection with these problems, researchers want to develop sustainable business strategies and improve existing business strategies by using PASTEL Analysis and Porter's 5 Forces Analysis to identify events and information that occur in the company's external business environment and use Resources / Capability analysis tools and VRIN Analysis to identify events and information that occur in the internal environment and then use SWOT and TOWS analysis to recommend business strategies using 5 indicators, namely (1) Managerial, (2) Marketing, (3) Technological, (4) R&D and Innovation, and ( 5) Human Resources as a benchmark for the company's operational activities in creating a company's competitive advantage.The analysis shows that Pelindo 3 has the opportunity to develop maritime ecosystems by collaborating with stakeholders including customers and conducting research and development by involving the general public.Thus, this research has contributed to managerial how to develop strategies and improve existing strategies.Keywords: Port Services, Changes in the Business Environment, Internal Analysis, External Analysis